2020
DOI: 10.1021/acs.est.0c03170
|View full text |Cite
|
Sign up to set email alerts
|

Novel Visible Light-Driven Photocatalytic Chlorine Activation Process for Carbamazepine Degradation in Drinking Water

Abstract: If it is the author's pre-published version, changes introduced as a result of publishing processes such as copy-editing and formatting may not be reflected in this document. For a definitive version of this work, please refer to the published version. A novel visible-light-driven photocatalytic chlorine activation process for carbamazepine degradation in drinking water

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(54 citation statements)
references
References 50 publications
0
53
0
Order By: Relevance
“…Strangely, this result is inconsistent with previously reported EPR test results showing that the signal of DMPO−HO • adducts in the solar/chlorine system can be observed in the presence of g-C 3 N 4 but not in the solar/chlorine system. 38,39 Xiao et al confirmed that the electrons generated by the photoexcitation of g-C 3 N 4 can be significantly cleared by O 3 to produce additional HO • . 40 Figure 4 is obtained on the basis of free-radical quenching data.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Strangely, this result is inconsistent with previously reported EPR test results showing that the signal of DMPO−HO • adducts in the solar/chlorine system can be observed in the presence of g-C 3 N 4 but not in the solar/chlorine system. 38,39 Xiao et al confirmed that the electrons generated by the photoexcitation of g-C 3 N 4 can be significantly cleared by O 3 to produce additional HO • . 40 Figure 4 is obtained on the basis of free-radical quenching data.…”
Section: Resultsmentioning
confidence: 99%
“…g-C 3 N 4 significantly promotes electron removal by O 3 due to the great gap in redox potential between the conduction band of g-C 3 N 4 and O 3 . Therefore, g-C 3 N 4 exhibits a strong synergistic effect with O 3 under visible light irradiation by improving the separation efficiency of photogenerated holes and electrons and accelerates the self-decomposition of O 3 , consequently accelerating the degradation of pollutants . Also, ozone contributes a lot, so we have to do experiments or tests to prove that ozone has a real effect on carbamazepine degradation.…”
Section: Resultsmentioning
confidence: 99%
“…The degradation of HClO via reaction with e CB − , or superoxide radical anions (O 2 •− ) also results in the formation of • OH [ 87 , 88 ], which may explain the increased r 0 7-HC for ZnO. Active chlorine species formation and photocatalytic reactions are complex, depending on many parameters [ 88 , 89 , 90 ], and require further investigation. Moreover, the positive effect of Cl − was observed only in the case of 365 nm radiation.…”
Section: Resultsmentioning
confidence: 99%
“…An electric-driven AOP mechanism uses electric energy (either from on-grid electricity or solar cell) to produce ROS for pollutant degradation and microbial disinfection through an electrochemical process (Lin et al, 2018;Liu et al, 2019a;Yang, 2020). With adequate solar energy in rural areas, light-driven and solar cells-powered electric-driven AOPs are the most suitable options for decentralized water treatment (Cheng et al, 2020;Chu et al, 2019;Nie et al, 2016). However, solar energy is unreliable due to sunlight fluctuation and overdependence, which led to a large construction footprint, and additional costs from installing storage devices (e.g., battery and capacitor) during solar energy utilization (Guerin, 2017;Zhang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%